Immunoglobulin A Isotype of Antiphospholipid Antibodies Does Not Provide Added Value for the Diagnosis of Antiphospholipid Syndrome in a Chinese Population - Hu, Chaojun; Li, Xi; Zhao, Jiuliang; Wang, Qian; Li, Mengtao; Tian, Xinping; Zeng, Xiaofeng (Frontiers in Immunology, 2020)
Objective: antiphospholipid syndrome (APS) is characterized by the presence of anti-phospholipid (aPL) antibodies. However, the relationship between the immunoglobulin (Ig) A isotype of aPL positivity and its clinical utility in APS diagnosis is controversial. Presently, we determine the clinical utility of IgA-aPL from consecutive patients in a large cohort from the Chinese population and patients with APS whose aPL profiles were obtained. Methods: The detection of anticardiolipin (aCL) and anti-β2 glycoprotein-Ⅰ (aβ2GPⅠ) antibodies of the IgA/IgG/IgM isotype by paramagnetic particle chemiluminescent immunoassay was carried out in sera from 7293 subjects. 153 primary APS (PAPS) patients and 59 patients with secondary APS (SAPS) were included in this study. Results: In total, 1082 out of 7293 (2.55%) subjects had a positive IgA-aPL test, and the prevalence of isolated IgA-aPL was 0.29% (21/7293) in the general population. The prevalence of IgA-aPL in the PAPS patients was 12.42% (19/153); however, only one patient (0.65%) presented with isolated IgA-aPL. Fifty (25.9%) of the SAPS had IgA-aPL, none of whom lacked IgG/IgM-aPL. The combination of the IgA isotype and the IgG/IgM isotype did not increase the diagnostic performance when compared with the IgG/IgM isotype of aCL or aβ2GPⅠ, respectively. IgA-aPL was not associated with clinical manifestation in patients with APS. Conclusion: Isolated IgA-aPL is rare in the general population as well as in patients with APS. Whether in the laboratory or in clinical practice, the presence of IgA-aPL does not provide added value for the diagnosis of APS in the Chinese population.